2010
DOI: 10.1111/j.1399-3038.2009.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rhinitis‐related symptoms in Latin American children – Results of the International Study of Asthma and Allergies in Childhood (ISAAC) phase three

Abstract: The aim of this study was to evaluate the prevalence of rhinitis-related symptoms among children living in different parts of Latin America (LA) considering all centers involved in ISAAC Phase Three (Ph3). 93,851 children (6-7 yr-old) from 35 centers in 14 LA countries and 165,917 adolescents (13-14 yr-old) from 56 centers in 17 LA countries were enrolled. The mean prevalence rate of current rhinoconjunctivitis was 12.7% and ranged from 5.5% in Rosario City (Argentina) to 21.2% in Caracas (Venezuela) for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 18 publications
4
65
1
8
Order By: Relevance
“…The prevalence of current rhinoconjunctivitis in adolescents varied 5-fold (from 8.9% in São Paulo West [Brazil] to 45.1% in Asuncion [Paraguay]) and 3.7-fold for the 6-7-year-old children (from 5.5% in Rosario City [Argentina] to 20.4% in Caracas [Venezuela]) (Table 2). 31…”
Section: Rhinitis and Isaac Phase I And Iiimentioning
confidence: 99%
“…The prevalence of current rhinoconjunctivitis in adolescents varied 5-fold (from 8.9% in São Paulo West [Brazil] to 45.1% in Asuncion [Paraguay]) and 3.7-fold for the 6-7-year-old children (from 5.5% in Rosario City [Argentina] to 20.4% in Caracas [Venezuela]) (Table 2). 31…”
Section: Rhinitis and Isaac Phase I And Iiimentioning
confidence: 99%
“…These characteristics together with the varying altitude divide the country according to the National Geographic Institute ( Instituto Nacional de Estadística y Geografía , INEGI) in six climate zones [6]. The ISAAC studies found a prevalence of rhinitis in Mexican children between 11.6-15.4% and asthma-like symptoms between 8.5-15.6% [1,7,8]. Allergic rhinitis risk factors and economic impact have been documented in that country [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…En el caso de Colombia, múltiples estudios demuestran un posible incremento en la prevalencia de las mismas (5)(6)(7). Entre el 5% y el 15% de los lactantes muestran síntomas sugestivos de reacciones adversas a las PLV, mientras que las estimaciones de la prevalencia real de la APLV varían del 2% al 7,5%, cifras que van en aumento en todos los países (8).…”
Section: Introductionunclassified